Voices of unbelief: documents from atheists and agnostics - McGowan, Dale (Voices of an Era, 2012)
This book spotlights individual expressions of atheist, agnostic, and secular humanist opinion, both public and private, to shed light on the phenomenon of religious disbelief throughout history and across cultures